2015
DOI: 10.1186/s12967-015-0398-z
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin exerts a marked antitumor effect in cMet-overexpressing patient-derived tumor xenograft models of gastric cancer

Abstract: BackgroundAberrated activation of cMet in gastric cancer contributes to tumor growth, angiogenesis and metastasis. cMet-overexpressing gastric cancer has a poor prognosis because of high tumor metastasis and limited therapeutic options. Luteolin is a common dietary flavonoid with antitumor properties. However, the antitumor effect of luteolin on cMet-overexpressing gastric cancer remain unclear.MethodsTwo cMet-overexpressing patient-derived human tumor xenograft (PDTX) models of gastric cancer were established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 37 publications
2
40
0
1
Order By: Relevance
“…*p < 0.05 and **p < 0.01 indicate a significant difference from the control group compounds targeting EMT and angiogenesis have been the efficient therapeutic approach for the treatment of metastatic cancers . Luteolin, a flavonoid that is found in more than 300 plant species, has recently been shown to inhibit a variety of cancers, both in vitro and in vivo, with little to minimal toxicity (Lu et al, 2015;Ruan et al, 2012). Previous studies have shown that luteolin inhibits metastasis of triple-negative breast cancer cells through suppressing EMT (Cook et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…*p < 0.05 and **p < 0.01 indicate a significant difference from the control group compounds targeting EMT and angiogenesis have been the efficient therapeutic approach for the treatment of metastatic cancers . Luteolin, a flavonoid that is found in more than 300 plant species, has recently been shown to inhibit a variety of cancers, both in vitro and in vivo, with little to minimal toxicity (Lu et al, 2015;Ruan et al, 2012). Previous studies have shown that luteolin inhibits metastasis of triple-negative breast cancer cells through suppressing EMT (Cook et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This latter finding is in agreement with Bagli et al30 and Pratheeshkumar et al,34 who reported that low concentrations of LU (10–20 µM) acted as both a potent PI3K inhibitor and an inhibitor of metalloproteinase MMP9. Additional evidence implicates downregulation of PI3K phosphorylation and MMP9 as being responsible for the anti-invasive capacity of LU, perhaps explaining its ability to reduce the invasive potential of various cancer cell lines in vitro 3842. Because the VEGF-induced PI3K pathway mediates cell survival, migration, and proliferation, we propose that our findings that LU inhibits TNBC cell migration support the notion that it acts via multiple mechanisms likely potentiated through blockade of PI3K phosphorylation and/or MMP-mediated VEGF signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Along with its antioxidant and anti‐inflammatory properties, luteolin has demonstrated anticancer effects in a variety of types of cancer through several mechanisms including inducing cell death, slowing cell proliferation and halting cell growth. Several studies have shown that luteolin down‐regulates Akt phosphorylation in gastric, breast, brain and other cancer cell lines .…”
mentioning
confidence: 99%